Harsh parenting among veterans: parents' military-related PTSD, mentalization, and pre-military trauma - Wang, Xiafei; Liu, Qingyang; Merrin, Gabriel J.; Keller, Amanda; Yoon, Dalhee; Henderson, Ava (Frontiers in Psychology, 2023)
Objectives: Veteran parents experiencing posttraumatic stress disorder (PTSD) may resort to harsh parenting. The indirect pathway from parental military-related PTSD to harsh parenting, and the moderating role of parents' pre-military trauma histories, has been less explored. Informed by mentalization theory, as well as trauma-sensitive and posttraumatic growth perspectives, we aim to explore the associations between veteran parents' military-related PTSD, mentalization, harsh parenting, and prior trauma before military service. Methods: Data were collected from an online research panel of 509 veteran parents with children under 10. We employed Structural Equation Models to test indirect and moderating effects. Results: We identified an indirect effect of parental pre-mentalization from military PTSD to harsh parenting (corporal punishment: b = .35, p < .001, 95% CI [.23, .46]; psychological aggression: b = .14, p < .001, 95% CI [.09, .19]). Multi-group analysis on four parent groups (parents with only pre-military physical trauma, parents with only premilitary psychological trauma, parents with both pre-military physical and psychological trauma, and parents with no pre-military physical or psychological trauma) highlighted differences in these associations, particularly between parents with only pre-military physical trauma and those without any physical and psychological trauma. The military-related PTSD effects on psychological aggression, corporal punishment, and pre-mentalization were all significantly higher for parents without pre-military physical and psychological trauma. Conclusion: Modifying parents' interpretation of their child's mental states can potentially counteract the effects of veterans' military PTSD on harsh parenting. Family-based programs should be created considering veteran parents' pre-military trauma histories.